2002
DOI: 10.1300/j030v11n03_18
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Application of Electronic Nose for Freshness Monitoring of Whole Redfish (Sebastes marinus) Stored in Ice and Modified Atmosphere Bulk Storage

Abstract: An electronic nose with electrochemical gas sensors (CO, NH 3 , SO 2 and H 2 S) was used as a rapid technique to monitor changes in the headspace of whole ungutted redfish (Sebastes marinus) stored in ice and under various conditions of modified atmosphere (MA) bulk storage (CO 2 /N 2 :60/40). The precision of the electronic nose measurements was determined using standard compounds (ethanol, trimethylamine, acetaldehyde and dimethyldisulfide). The response of the CO sensor, suggesting the formation of alcohols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The PC1 trend as a function of storage time for each temperature seems to be characterized by a lag phase and a steep slope after it. This can partly be explained by the low sensitivity of the sensors (Ó lafsdó ttir, Li, Lauzon, & Jonsdottir, 2002) and the fact that microbial cell counts are needed to produce metabolites in high enough concentrations to be detected by the sensors (Ó lafsdó ttir et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The PC1 trend as a function of storage time for each temperature seems to be characterized by a lag phase and a steep slope after it. This can partly be explained by the low sensitivity of the sensors (Ó lafsdó ttir, Li, Lauzon, & Jonsdottir, 2002) and the fact that microbial cell counts are needed to produce metabolites in high enough concentrations to be detected by the sensors (Ó lafsdó ttir et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The response of the CO sensor was higher than the other sensors' responses (H 2 S, SO 2 , and NH 3 ), and a significant increase (p < 0.05) was first observed between days 7 and 10; thereafter, a continuous increase occurred. Earlier studies have shown that the main classes of spoilage indicator compounds present in the headspace of whole fish can be estimated based on the individual sensor responses (5). Selected standard compounds representing the main classes of compounds causing spoilage odors showed that the CO sensor is sensitive to alcohols, aldehydes, and esters.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic nose instrument (FreshSense, Bodvaki-Maritech, Ko ´pavogur, Iceland) is based on four electrochemical gas sensors: CO, H 2S, SO2 (Dra ¨ger, Luebeck, Germany), and NH3 (City Technology, Portsmouth, Britain). The measurements were performed at RT as described earlier (5). Approximately 500 g of fish fillets was weighed and tempered for 30 min in the sampling container (2.3 L, Ø 17 cm).…”
Section: Methodsmentioning
confidence: 99%
“…and Alteromonas spp 5. and more specifically Shewanella putrefaciens and Photobacterium phosphoreum 6, 7. These bacteria generate odours by producing alcohols, carbonyls, esters and sulfur compounds8–10 corresponding to different kinds of odour such as flat and neutral odours, and then rancid, putrid odours or odours of ammonia or sulfur changing the flavour and taste of fish during storage 11–13.…”
Section: Introductionmentioning
confidence: 99%